Teen Titans: Beast Boy Loves Raven - Book 3 Beast Boy loves Raven - Garcia, Kami; Picolo, Gabriel; Haynes, Rob; Calderon, David; Downie, Gabriela (Burbank, CA : DC Comics, 2022)
While Raven Roth is finding a way to get rid of her demon father Trigon, Garfield Logan is understanding his newly found shapeshifting ability, and when their paths cross in Nashville they both feel a strong connection to one another.
Keywords: Raven -- (Fictitious character) -- Comic books, strips, etc; Beast Boy -- (Fictitious character) -- Comic books, strips, etc; Raven -- (Fictitious character) -- Fiction; Beast Boy -- (Fictitious character) -- Fiction; Superheroes -- Comic books, strips, etc; Ability -- Comic books, strips, etc; Love -- Comic books, strips, etc; Secrecy -- Comic books, strips, etc; Superheroes -- Fiction; Ability -- Fiction; Love -- Fiction; Secrets -- Fiction; Cartoons and comics; Nashville (Tenn.) -- Comic books, strips, etc; Nashville (Tenn.) -- Fiction; Superhero comics; Romance comics; Graphic novels; Comics (Graphic works)